2007
DOI: 10.1017/s0007114507812037
|View full text |Cite
|
Sign up to set email alerts
|

A maternal ‘junk food’ diet in pregnancy and lactation promotes an exacerbated taste for ‘junk food’ and a greater propensity for obesity in rat offspring

Abstract: Obesity is generally associated with high intake of junk foods rich in energy, fat, sugar and salt combined with a dysfunctional control of appetite and lack of exercise. There is some evidence to suggest that appetite and body mass can be influenced by maternal food intake during the fetal and suckling life of an individual. However, the influence of a maternal junk food diet during pregnancy and lactation on the feeding behaviour and weight gain of the offspring remains largely uncharacterised. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
367
4
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(417 citation statements)
references
References 22 publications
34
367
4
8
Order By: Relevance
“…However, offspring exposed to SFA-rich pre-or postweaning diets (S/S, S/C, and C/S), consumed significantly less food compared with offspring exposed to chow throughout the study (C/C). Previous studies have reported increased adiposity and body weight in male and female offspring of mothers fed an SFA-rich diet during pregnancy and lactation in different rat models (9,27,37). It has also been shown earlier that rodents, like humans, can regulate their food intake and energy expenditure to maintain a set body weight (33).…”
Section: Discussionmentioning
confidence: 95%
“…However, offspring exposed to SFA-rich pre-or postweaning diets (S/S, S/C, and C/S), consumed significantly less food compared with offspring exposed to chow throughout the study (C/C). Previous studies have reported increased adiposity and body weight in male and female offspring of mothers fed an SFA-rich diet during pregnancy and lactation in different rat models (9,27,37). It has also been shown earlier that rodents, like humans, can regulate their food intake and energy expenditure to maintain a set body weight (33).…”
Section: Discussionmentioning
confidence: 95%
“…Since we have also observed hyperphagia in the offspring of obese mice fed the same diet [34], persistent alteration in regulation of appetite-controlling pathways may play a causative role in the development of increased adiposity in both species. Food intake has not been rigorously assessed by others addressing the same hypothesis [28], although Bayol et al [35,41] have implicated altered food preference (for 'junk food' over standard chow) in development of obesity in offspring of dams fed the 'junk food' diet throughout pregnancy and lactation, but not when exposed to the diet during pregnancy only. Similarly no difference was shown in food intake in the offspring of obese dams exposed to this obesogenic diet during gestation alone [28].…”
Section: Discussionmentioning
confidence: 99%
“…One way to examine this is to see if a different, environmentally induced rat model of hyperphagia-induced obesity, without mutations in the CCK (or NPY) systems, shows a similar pattern. Bayol et al 49 provided rat dams with a 'cafeteria diet', which consisted of eight different types of palatable foods, together with their normal balanced chow from the first day of pregnancy. These dams exhibited hyperphagia and increased intake of foods rich in fat throughout pregnancy and lactation, compared to chowfed controls.…”
Section: Discussionmentioning
confidence: 99%